Ice Complex permafrost of MIS5 age in the Dmitry Laptev Strait coastal region (East Siberian Arctic). (1st September 2016) - Wetterich, Sebastian; Tumskoy, Vladimir; Rudaya, Natalia; Kuznetsov, Vladislav; Maksimov, Fedor; Opel, Thomas; Meyer, Hanno; Andreev, Andrei A.; Schirrmeister, Lutz
Abstract: Ice Complex deposits (locally known as the Buchchagy Ice Complex) are exposed at both coasts of the East Siberian Dmitry Laptev Strait and preserved below the Yedoma Ice Complex that formed during MIS3 and MIS2 (Marine Isotope Stage) and lateglacial-Holocene thermokarst deposits (MIS1). Radioisotope disequilibria ( 230 Th/U) of peaty horizons date the Buchchagy Ice Complex deposition to 126 + 16/−13 kyr and 117 + 19/−14 kyr until 98 ± 5 kyr and 89 ± 5 kyr. The deposit is characterised by poorly-sorted medium-to-coarse silts with cryogenic structures of horizontal ice bands, lens-like, and lens-like reticulated segregation ice. Two peaty horizons within the Buchchagy Ice Complex and syngenetic ice wedges (2–4 m wide, up to 10 m high) are striking. The isotopic composition (δ 18 O, δD) of Buchchagy ice-wedge ice indicates winter conditions colder than during the MIS3 interstadial and warmer than during MIS2 stadial, and similar atmospheric winter moisture sources as during the MIS2 stadial. Buchchagy Ice Complex pollen spectra reveal tundra-steppe vegetation and harsher summer conditions than during the MIS3 interstadial and rather similar vegetation as during the MIS2 stadial. Short-term climatic variability during MIS5 is reflected in the record. Even though the regional chronostratigraphic relationship of the Buchchagy Ice Complex to the Last Interglacial remains unclear because numerical dating is widely lacking, the present study indicates permafrost (Ice Complex) formation during MIS5 sensu lato, and its preservation afterwards. Palaeoenvironmental insights into past climate and the periglacial landscape dynamics of arctic lowlands in eastern Siberia are deduced from the record. Highlights: Permafrost aggradation during MIS5 sensu lato in arctic eastern Siberia. MIS5 Ice Complex peaty deposits dated by radioisotope disequilibria. MIS5 tundra-steppe vegetation mirrors MIS2-similar dry and cold summer conditions. MIS5 ground-ice stable isotope data mirrors warmer than MIS2 winter temperatures.